IJTIHAD DEWAN HISBAH PERSATUAN ISLAM DALAM HUKUM ISLAM - Abbas, Rafid (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2016)
Abstract: This article discusses the method of ijtihad (independent Islamic legal rasoning) practiced by Dewan Hisbah of Persatuan Islam from 1996-2009. Persatuan Islam (PERSIS â Islamic Unity)Â  is an Islamic renewal movement in Indonesia that is established in 1923. Although it is relatively small Islamic mass organization compared to Muhammadiyah and Nahdlatul Ulama, PERSIS also perform as fatwa issuing body (mufti) that answer queries from its members and affiliates on Islamic legal issues. This role is performed by Dewan Hisbah (supervisory board) that performs supervision, research and fatwa issuance within the organization.Â  In the span between 1996-2006, the board has issued many fatwas on some controversial legal issues, namely performing salat (prayer) in non-Arabic language, jumâah (congregational) prayer for travelers, raising hands during doâa (supplication), the interplay between zakat (obligatory alms) and tax, cash waqf (endowment) and inheritance from non-Muslim family. As a reform movement, Dewan Hisbah performs ijtihad, in which it directly deals with primary sources (the Qurâan and Hadith) and other ijtihad mechanisms in formulating legal opinions.Key words: Ijtihad, Dewan Hisbah, PERSIS, Islamic LawÂ Abstrak: Tulisan ini membahas tentang Ijtihad Dewan Hisbah Persatuan Islam dalam Hukum Islam pada Periode tahun 1996-2009. Persatuan Islam (PERSIS) merupakan salah satu gerakan pembaharuan yang berdiri pada tahun 1923 M. PERSIS melakukan ijtihad melalui Majelis Ulama Persis yang kemudian berganti nama menjadi Dewan Hisbah PERSIS. Dewan Hisbah adalah Lembaga Hukum Persatuan Islam yang berfungsi sebagai dewan pertimbangan, pengkajian syariâah, dan fatwa dalam jamâiyyah Persatuan Islam. Kajian hukum Dewan Hisbah PERSIS dari tahun 1996-2009, telah banyak melahirkan berbagai pemikiran hukum Islam, di antaranya hukum salat dengan dua bahasa, hukum salat Jumâat bagi musafir, mengangkat tangan ketika berdoa, posisi zakat dan pajak, wakaf uang, dan waris dari non muslim. Metode Dewan Hisbah dalam mengambil keputusan hukum adalah dengan mendasarkan pada al-Qurâan dan Hadis shahih, sebagai sumberÂ  utama hukum Islam, dan berijtihad terhadap masalah yang tidak ada nasnya.Kata Kunci: Ijtihad, Dewan Hisbah, PERSIS, Hukum Islam